The performances of cationic starch (CS) and sodium carboxymethyl celluloses (CMC-Na) as a dry strength additives (DSA) on A4 wastepaper - Main, Nor Mazlana; Hishamuddin, Nurfarhani; Marsi, Noraini; Esa, Mohd Faizal; Masrol, Shaiful Rizal (2024)
This study aims to identify the performances of cationic starch (CS) and sodium carboxymethyl celluloses (CMC-Na) as dry strength additives (DSA). The CS and CMC-Na were incorporated with to pulp slurry in different dosages (0.5% - 2.0%) during stock preparation. The basic weight of 80 g/m2 was made for each treatment. The results showed that the utilization of CMC-Na had better mechanical properties compared to the CS for all treatments. In general, apparent density and mechanical properties were significantly affected by the addition of DSA. However, through the observation of the experiment, the enhancing effect of CMCNa on mechanical properties of wastepaper was much higher than using CS except for tear strength. The FESEM imaging results can also help prove the best DSA used in wastepaper production